CORPORATE GOVERNANCE 2.0: THE ROLE OF ARTIFICIAL INTELLIGENCE IN FUTURE TRANSFORMATION - Mr. Rakesh Sharma,; Dr. Arun Kumar,; Dr. Richa Pandey,; Mr. Rahil Abbas, (IJRDO - Journal of Business Management, 2025)
This study looks at how corporate governance is being impacted by artificial intelligence (AI). The feasibility, acceptability, along with the obligation to automate board-level collective decision making are assessed from the viewpoints of business, technology, and society. Five possibilities for AI governance are suggested in the article: aided, enhanced, amplified, autonomous, and autopoietic intelligence. We evaluate the strengths and weaknesses of both human and machine learning, and we examine the consequences for future governance. The study ends with a request for participation from board members in determining the direction of AI governance.